Nanocomposite fracture analysis: Aligned Fe3O4-GNP nanoplatelets’ effects on KIC, GIC, CTODc, and fracture mechanisms in epoxy matrices - Tiwari A. (My University, 2025)
Epoxy nanocomposites are crucial in aerospace, enhancing structural performance, reducing weight, and improving fuel efficiency across various applications. They ensure safety, reliability, and optimal performance in critical aerospace systems. Optimizing fracture properties like crack growth resistance (KIC), critical stress intensity factor (GIC), and critical crack tip opening displacement (CTODc), is vital for safety, durability, and innovation, especially in epoxy nanocomposites under extreme conditions. This study examines how random Graphene Nanoplatelets (GNP) and aligned Fe3O4-GNP nanoplatelets impact the fracture resistance of epoxy nanocomposites. It analyzes various fracture properties and crack propagation mechanisms following ASTM D5045-99 standards for CT specimen toughness tests using a COD gauge, focusing on nanoparticle alignment and wt% loading effects. Neat epoxy has a KIC of 0.94 MPa m1/2, increasing to 1.20 with 0.600 wt% GNP. Aligned Fe3O4-GNP peaks at 1.49. the baseline GIC starts at 209 J/m2 and rises to 301 J/m2 with 0.600 wt% GNP, and notably to 419J/m2 with aligned Fe3O4-GNP. Aligned Fe3O4-GNP significantly enhances fracture properties by modifying stress distribution at primary crack fronts through mechanisms such as deflection, branching, and twisting. These findings offer crucial insights for improving epoxy nanocomposites in aerospace, ensuring increased safety, reliability, and performance in critical components. © 2024 Elsevier Ltd